The Effectiveness of Group Guidance Services Using Simulation Techniques to Improve Student Interpersonal Communication - Ustomi, Ahmad; Nur Wangid, Muhammad; Dyah Winarsih, Setyoningsih (Green Publisher Indonesia, 2024)
Background: Communication requires a reciprocal relationship between the delivery of the message and the recipient. In the family, school and social environment, individuals really need communication to support their daily activities. Purpose: This study aims to test the effectiveness of simulation technique group guidance to improve interpersonal communication of grade VII students of Mataram Kasihan Bantul Junior High School for the 2021/2022 Academic Year. Method: This research use a pre-experimental type quantitative experiment method with a one group pretest-posttest design. The data collection method used a questionnaire with a population of 99 students in class VII B, VII C and VII E. While the sample in this study took 12 students from the population using purposive sampling techniques, and the data analysis technique of this study used paired simple t-test analysis. Results: Based on the results of the paired simple t-test analysis, the average pretest result = 72.00 and the average posttest result = 89.83, which means that there is an average increase of 17.83. While the value of t = 24.908 with a sig value. (2 tailed) = 0.000 which means < 0.05. Thus Ha is accepted, meaning that there is a positive and significant influence so that the provision of group guidance services for effective discussion techniques to improve interpersonal communication of grade VII students at Mataram Kasihan Bantul Junior High School for the 2021/2022 Academic Year. Conclusion: The results of this study indicate that the provision of group guidance services using simulation techniques is effective for improving interpersonal communication for class VII students of Mataram Kasihan Middle School, Bantul, 2021/2022 Academic Year. Based on the results of the t-test analysis, the alternative hypothesis (Ha) is accepted, meaning that there is a positive and significant influence regarding the provision of group guidance services using simulation techniques to improve interpersonal communication for class VII students of SMP Mataram Kasihan Bantul Academic Year 2021/2022.